Activity Theory as a Challenge to Systems Design - Bødker, Susanne (DAIMI Report Series, 1990)
This paper suggests an improvement of the theoretical foundation of information systems research of the 1990s. This foundation is found in human activity theory. The paper deals with how human activity theory can help systems design change, theoretically and practically. Applying activity theory to systems design, certain cornerstones become apparent, on which future systems design practice and research need to build. The paper will discuss these cornerstones, and the implications of the new understanding for design practice and research.